Dispensing type heat-conducting wave-absorbing gel
By using a dispensed thermally conductive wave absorbing gel composed of components A and components B at a 1:1 mass ratio, the problem of unstable thermal conductivity and absorption rate after aging of the thermally conductive wave absorbing gel is solved, and the effect of high thermal conductivity and stable absorption rate is achieved, which is suitable for packaging of complex shapes and high power components.
Patent Information
- Application Number
- CN202411986651.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The existing thermal conductivity and absorption rate of existing thermal waveguide gels are unstable after aging, making it difficult to meet the heat dissipation and electromagnetic radiation shielding requirements of complex shapes and high-power components in electronic products.
A dispensing thermal absorption gel consisting of component A and component B in a mass ratio of 1:1. Component A includes vinyl silicone oil, catalyst and Fe/Al2O3 thermal absorption powder. Component B includes hydrogen-containing silicone oil for chain extension, hydrogen-containing silicone oil for cross-linking, inhibitors and Fe/Al2O3 thermal absorption powder. It is stirred and adjusted by a dual planetary mixer, and finally vulcanized at 120°C.
It realizes high thermal conductivity and stable absorption rate of thermal wave absorbing gel, and is suitable for packaging of opposite-sex surfaces and complex shapes, improving the heat dissipation and electromagnetic radiation shielding performance of electronic products.
Smart Images

Figure CN119799007A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat-conducting and wave-absorbing gel production, and in particular to a dispensing type heat-conducting and wave-absorbing gel. Background Art
[0002] With the rapid development of integrated circuit technology and assembly technology in the electronics industry, the integration of multiple heat sources has become common, and the heat sources are of different heights and shapes, which has increased the requirements for heterogeneous packaging of thermal conductive materials. In addition, electronic products are developing towards functional integration, and there are more and more components on circuit boards. As the power of electronic products increases, the requirements for electromagnetic radiation shielding between components are getting higher and higher. The single-thickness thermal conductive absorbing gasket cannot meet the heat dissipation requirements and thus the insulation performance of the bonding and packaging materials, which has promoted the industry's development of thermal conductive absorbing adhesives.
[0003] Thermally conductive wave-absorbing gel is a gel-like A / B component thermally conductive wave-absorbing material made of silicone composite thermally conductive wave-absorbing integrated filler through stirring, mixing and packaging. It adopts a dispensing design and is dispensed with a mixing nozzle when in use. It is easy to use and can realize automated production. It is generally a two-component paste that can fill irregular and complex shapes, which is its advantage over thermally conductive gaskets. In addition, its formula design is more diversified than that of thermally conductive gaskets. The assembly stress of silicone material is extremely low. After vulcanization, due to its low hardness and very small expansion coefficient, it can improve the stability of the circuit board. During the molding process of thermally conductive gaskets, there will be problems such as unqualified dimensions and cutting edges, and the utilization rate of raw materials is low. The automated dispensing of thermally conductive wave-absorbing gel can accurately control the dosage and the utilization rate of raw materials is high.
[0004] The conventional production process of thermal conductive absorbing materials is to add two functional powders into the silicone system at the same time: a composite material made of absorbing powder and thermal conductive powder and corresponding additives. The product can achieve low interfacial thermal resistance and electromagnetic absorbing performance under low pressure, can fill gaps, and play a role in insulation, shock absorption, and sealing. The addition mode of the two powders has the characteristics of one increase and the other decrease in product performance. For example, when the amount of thermal conductive powder added is large, the thermal conductivity of the product is strong and the absorbing performance is weak; when the amount of absorbing powder added is large, the absorbing performance of the product is strong and the thermal conductivity is weak. There will definitely be a phenomenon of one increase and one decrease. Summary of the invention
[0005] The object of the present invention is to provide a dispensing type heat-conducting and wave-absorbing gel, which has good heat-conducting and wave-absorbing capabilities, and the thermal conductivity and wave-absorbing rate of the heat-conducting gel are stable after aging.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A dispensing type heat-conducting and wave-absorbing gel, composed of component A and component B in a mass ratio of 1:1; The raw materials of component A include: 100 parts by weight of vinyl silicone oil, 0.4 to 0.6 parts by weight of catalyst, Fe / Al 2 O 3 70-80 parts by weight of thermal conductive wave absorbing powder; The raw materials of component B include: 20 parts by weight of hydrogenated silicone oil for chain extension, 80 parts by weight of hydrogenated silicone oil for crosslinking, 0.4-0.6 parts by weight of inhibitor, Fe / Al 2 O 3 70-80 parts by weight of heat-conducting and wave-absorbing powder. The catalyst is used to accelerate the curing speed, and the inhibitor is used to control the reaction speed and adjust the operation time.
[0007] The viscosity of vinyl silicone oil is 100-1000 mPa·s, the viscosity of hydrogen-containing silicone oil for chain extension is 500-1000 mPa·s, and the viscosity of hydrogen-containing silicone oil for cross-linking is 10-200 mPa·s.
[0008] The catalyst is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane.
[0009] The inhibitor is 1-ethynylcyclohexanol.
[0010] The Fe / Al 2 O 3 The preparation method of thermal conductive wave absorbing powder is as follows: (1) 500 mL of deionized water, 1.0-5.0 g of Tween 40, and 50-55 g of micron-sized carbonyl Fe powder were added to a beaker in sequence, stirred for 10-24 h, and centrifuged to obtain Tween-modified carbonyl iron powder; (2) 100 ml of anhydrous ethanol, 10-12 g of Tween-modified carbonyl iron powder, 1-5 ml of triethylamine, and 2-3 ml of 0.1-1.0 mol / l ethanol aqueous solution of aluminum isopropoxide are sequentially added to a beaker, stirred evenly, filtered, and solids are collected; (3) The collected solid is washed with ethanol or deionized water for multiple times and vacuum dried; finally, the dried product is placed in a tube furnace, calcined at high temperature, and the product is collected after cooling to room temperature to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder.
[0011] The present invention uses Tween 40 surface modification to quickly prepare Fe / Al 2 O 3 Magnetic metal core-shell particles, including Fe with good electromagnetic and thermal conductivity and Al with excellent thermal conductivity 2 O 3 The combined composite material acts as a filler and plays the dual functions of heat conduction and wave absorption.
[0012] In step (2), the solvent ethanol aqueous solution in the ethanol aqueous solution of aluminum isopropoxide is prepared by mixing anhydrous ethanol and water in a mass ratio of 1:1.
[0013] In step (3), high temperature calcination is: heating to 800-850°C at a heating rate of 10-20°C / min, and keeping warm for 2 hours under nitrogen protection.
[0014] The processing method of component A is as follows: vinyl silicone oil, catalyst and Fe / Al 2 O 3 The thermal conductive and microwave absorbing powder was stirred and mixed in a double planetary mixer, and the fumed silica was added to adjust the viscosity to 2.0×10 5 ~5.0×10 6 mPa·s, and finally vacuum degassing.
[0015] The processing method of the B component is: hydrogenated silicone oil for chain extension, hydrogenated silicone oil for crosslinking, inhibitor and Fe / Al 2 O 3 The thermal conductive and microwave absorbing powder was stirred and mixed in a double planetary mixer, and the fumed silica was added to adjust the viscosity to 2.0×10 5 ~5.0×10 6 mPa·s, and finally vacuum degassing.
[0016] The present invention uses a simple and feasible method to prepare oxide-coated core-shell spherical Fe / Al 2 O 3 The composite powder maintains the original Fe magnetic properties while having a certain insulation property, thus solving the problems of large high-frequency eddy current loss and poor magnetic permeability stability of pure Fe powder. At the same time, a single core-shell structure powder coated with ceramic is used to replace the conventional absorbing powder plus ceramic thermal conductive powder to achieve a new product structure that integrates insulation, thermal conductivity and wave absorption.
[0017] The invention has the advantages of simple preparation process, integrated heat conduction and wave absorption, easy to adjust dosage, high thermal conductivity, stable thermal conductivity and wave absorption, and suitable for anisotropic surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The following are comparison pictures of the microscopic morphology of micron-sized carbonyl Fe powders treated differently; (a) morphology of original Fe powder; (b) morphology of Fe powder in Example 2; (c) morphology of Fe powder in Example 3. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described in detail below through specific embodiments.
[0020] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.
[0021] All viscosities in the present invention are values tested at 20°C.
[0022] Embodiment 1: Take 500ml deionized water, 1.0g Tween 40, 50g micron-grade carbonyl Fe powder (D50 is 5um, such as Figure 1 a) adding them into a beaker in sequence, stirring for 10 hours, and centrifuging to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 10g of Tween-modified carbonyl iron powder, 1ml of triethylamine, and 2ml of 0.1mol / l ethanol aqueous solution of aluminum isopropoxide (ethanol: water = 1:1 mass ratio) to the beaker. Continue to stir electrically, filter, and collect the solid; wash the collected solid with ethanol 5 times to remove the uncoated and hydrolyzed colloidal particles. Dry the solid at 80℃ in vacuum for 24h. Finally, place the dried product in a tube furnace, heat it to 800℃ at a heating rate of 15℃ / min, and heat it in a high-purity N 2 Keep the temperature for 2h, cool to room temperature and collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder.
[0023] Preparation of a dispensing type thermally conductive and microwave absorbing gel: Preparation of component A: Add 100 g of 500 mPa·s viscosity vinyl silicone oil, 0.5 g of platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane (commercially available, concentration 3000 ppm), Fe / Al 2 O 3 After 75g of thermal conductive and wave absorbing powder was added, it was stirred in a double planetary mixer for 1.0h and the viscosity was adjusted to 2.5×10 5 mPa·s, and then vacuum degassing.
[0024] Preparation of component B: Add 20 g of 500 mPa·s hydrogenated silicone oil for chain extension, 80 parts of 100 mPa·s hydrogenated silicone oil for crosslinking, 0.5 g of 1-ethynyl cyclohexanol, and Fe / Al 2 O 3 After 75g of thermal conductive and wave absorbing powder was added, it was stirred in a double planetary mixer for 1.0h and the viscosity was adjusted to 2.5×10 5 mPa·s, and then vacuum degassing.
[0025] Finally, the present invention extrudes component A and component B through an AB hose and an AB glue gun at a mass ratio of 1:1 to mix evenly, then vacuumizes the mixture to remove bubbles and presses it into a 2 mm sheet, and vulcanizes it at 120° C. for 0.5 h to obtain a test sheet sample (test results are shown in Table 1).
[0026] Embodiment 2: 500 ml of deionized water, 3.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) were added to a beaker in sequence, stirred for 10 h, and centrifuged to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 10g of Tween-modified carbonyl iron powder, 1ml of triethylamine, and 2ml of 0.1mol / l isopropanol aluminum ethanol aqueous solution (ethanol: water = 1:1 mass ratio) to the beaker. Continue to stir electrically, filter, and collect the solid; wash the collected solid with deionized water 5 times to remove the uncoated and hydrolyzed colloidal particles. Dry the solid at 80℃ in vacuum for 24h. Finally, place the dried product in a tube furnace, heat it to 800℃ at a heating rate of 15℃ / min, and heat it in a high-purity N 2 Keep the temperature for 2h, cool to room temperature and collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder (such as Figure 1 b).
[0027] The preparation method of the dispensing type thermal conductive wave absorbing gel is the same as that in Example 1.
[0028] Embodiment 3: 500 ml of deionized water, 5.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) were added to a beaker in sequence, stirred for 10 h, and centrifuged to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 10g of Tween-modified carbonyl iron powder, 1ml of triethylamine, and 2ml of 0.1mol / l isopropanol aluminum ethanol aqueous solution (ethanol: water = 1:1 mass ratio) to the beaker. Continue to stir electrically, filter, and collect the solid; wash the collected solid with deionized water 5 times to remove the uncoated and hydrolyzed colloidal particles. Dry the solid at 80℃ in vacuum for 24h. Finally, place the dried product in a tube furnace, heat it to 800℃ at a heating rate of 15℃ / min, and heat it in a high-purity N 2 Keep the temperature for 2h, cool to room temperature and collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder.
[0029] The preparation method of the dispensing type thermal conductive wave absorbing gel is the same as that in Example 1.
[0030] Embodiment 4: The difference between this example and Example 2 is that 500 ml of deionized water, 3.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) are added to a beaker in sequence, stirred for 24 hours, and centrifuged to obtain Tween-modified carbonyl iron powder; the rest is the same as Example 2.
[0031] Embodiment 5: 500 ml of deionized water, 3.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) were added to a beaker in sequence, stirred for 24 h, and centrifuged to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 10g of Tween-modified carbonyl iron powder, 2.5ml of triethylamine, and 2ml of 0.1mol / l isopropanol aluminum ethanol aqueous solution (ethanol: water = 1:1 mass ratio) to the beaker. Continue to stir electrically, filter, and collect the solid; wash the collected solid with deionized water 5 times to remove the uncoated and hydrolyzed colloidal particles. Dry the solid at 80℃ in vacuum for 24h. Finally, place the dried product in a tube furnace, heat it to 800℃ at a heating rate of 15℃ / min, and heat it in high-purity N 2 Keep the temperature for 2h, cool to room temperature and collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder.
[0032] The preparation method of the dispensing type thermal conductive wave absorbing gel is the same as that in Example 1.
[0033] Embodiment 6: 500 ml of deionized water, 3.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) were added to a beaker in sequence, stirred for 24 h, and centrifuged to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 10g of Tween-modified carbonyl iron powder, 5.0ml of triethylamine, and 2ml of 0.1mol / l isopropanol aluminum ethanol aqueous solution (ethanol: water = 1:1 mass ratio) to the beaker. Continue to stir electrically, filter, and collect the solid; wash the collected solid with ethanol or deionized water 5 times to remove the uncoated and hydrolyzed colloidal particles. Dry the solid at 80℃ in vacuum for 24h. Finally, place the dried product in a tube furnace, heat it to 800℃ at a heating rate of 15℃ / min, and heat it in a high-purity N 2 Keep the temperature for 2h, cool to room temperature and collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder.
[0034] The preparation method of the dispensing type thermal conductive wave absorbing gel is the same as that in Example 1.
[0035] Embodiment 7: 500 ml of deionized water, 3.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) were added to a beaker in sequence, stirred for 24 h, and centrifuged to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 12g of Tween-modified carbonyl iron powder, 2.5ml of triethylamine, and 3ml of 0.5mol / l isopropanol aluminum ethanol aqueous solution (ethanol: water = 1:1 mass ratio) to the beaker. Continue to stir electrically, filter, and collect the solid; wash the collected solid with ethanol or deionized water 5 times to remove the uncoated and hydrolyzed colloidal particles. Dry the solid at 80℃ in vacuum for 24h. Finally, place the dried product in a tube furnace, heat it to 850℃ at a heating rate of 10℃ / min, and heat it in a high-purity N 2 Keep the temperature for 2h, cool to room temperature and collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder (such as Figure 1 c).
[0036] The preparation method of the dispensing type thermal conductive wave absorbing gel is the same as that in Example 1.
[0037] Embodiment 8: 500 ml of deionized water, 3.0 g of Tween 40, and 50 g of micron-grade carbonyl Fe powder (D50 is 5 um) were added to a beaker in sequence, stirred for 24 h, and centrifuged to obtain Tween-modified carbonyl iron powder; Then add 100ml of anhydrous ethanol, 10g of Tween-modified carbonyl iron powder, 2.5ml of triethylamine, and 2ml of 1.0mol / l isopropanol aluminum ethanol aqueous solution (ethanol: water = 1:1 mass ratio) to the beaker in sequence. Continue to stir electrically, filter, and collect the solid; wash the collected solid with ethanol or deionized water 5 times to remove uncoated and hydrolyzed colloidal particles. Dry the solid in a vacuum at 80°C for 24h. Finally, place the dried product in a tubular furnace, heat to 800°C at a heating rate of 20°C / min, and keep it warm for 2h under high-purity N2. After cooling to room temperature with the furnace, collect the product to obtain Fe / Al 2 O 3 Thermally conductive and microwave absorbing powder.
[0038] The preparation method of the dispensing type thermal conductive wave absorbing gel is the same as that in Example 1.
[0039] Embodiment 9: The difference between this embodiment and embodiment 2 is that: Preparation of a dispensing type thermally conductive and microwave absorbing gel: Preparation of component A: Add 100 g of 1000 mPa·s viscosity vinyl silicone oil, 0.6 g of platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane (commercially available, concentration 3000 ppm), Fe / Al2 O 3 After 80g of thermal conductive and wave absorbing powder was mixed in a double planetary mixer for 1.0h, the viscosity was adjusted to 5.0×10 6 mPa·s, after vacuum degassing.
[0040] Preparation of component B: Add 20 g of 1000 mPa·s hydrogenated silicone oil for chain extension, 80 g of 200 mPa·s hydrogenated silicone oil for crosslinking, 0.6 g of 1-ethynyl cyclohexanol, and Fe / Al 2 O 3 After 80g of thermal conductive and wave absorbing powder was mixed in a double planetary mixer for 1.0h, the viscosity was adjusted to 5.0×10 6 mPa·s, after vacuum degassing.
[0041] Finally, the present invention extrudes component A and component B through an AB hose and an AB glue gun at a mass ratio of 1:1 to mix evenly, then vacuumizes the mixture to remove bubbles and presses it into a 2 mm sheet, and vulcanizes it at 120° C. for 0.5 h to obtain a test sheet sample (test results are shown in Table 1).
[0042] Embodiment 10: The difference between this embodiment and embodiment 2 is that: Preparation of a dispensing type thermally conductive and microwave absorbing gel: Preparation of component A: Add 100 g of 100 mPa·s viscosity vinyl silicone oil, 0.4 g of platinum (0)-1,3-diethylene-1,1,3,3-tetramethyldisiloxane (commercially available, concentration 3000 ppm), Fe / Al 2 O 3 After 70g of thermal conductive and wave absorbing powder was added, it was stirred in a double planetary mixer for 1.0h and the viscosity was adjusted to 2.0×10 5 mPa·s, after vacuum degassing.
[0043] Preparation of component B: Add 20 g of 500 mPa·s hydrogenated silicone oil for chain extension, 80 g of 10 mPa·s hydrogenated silicone oil for crosslinking, 0.4 g of 1-ethynyl cyclohexanol, and Fe / Al 2 O 3 After 70g of thermal conductive and wave absorbing powder was added, it was stirred in a double planetary mixer for 1.0h and the viscosity was adjusted to 2.0×10 5 mPa·s, after vacuum degassing.
[0044] Finally, the present invention extrudes component A and component B through an AB hose and an AB glue gun at a mass ratio of 1:1 to mix evenly, then vacuumizes the mixture to remove bubbles and presses it into a 2 mm sheet, and vulcanizes it at 120° C. for 0.5 h to obtain a test sheet sample (test results are shown in Table 1).
[0045] Comparative Example 1: The difference between this embodiment and embodiment 2 is that: Preparation of a dispensing type thermally conductive and microwave absorbing gel: Preparation of component A: Add 100 g of 500 mPa·s viscosity vinyl silicone oil, 0.5 g of platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane (commercially available, concentration 3000 ppm), 75 g (35 g of Tween-modified carbonyl iron powder, Al 2 O 3 After 40g of powder, the mixture was stirred in a double planetary mixer for 1.0h, and the viscosity was adjusted to 2.5×10 5 mPa·s, after vacuum degassing.
[0046] Preparation of component B: Add 20 g of 500 mPa·s hydrogenated silicone oil for chain extension, 80 g of 100 mPa·s hydrogenated silicone oil for crosslinking, 0.5 g of 1-ethynyl cyclohexanol, and Fe / Al 2 O 3 After 75g of thermal conductive and wave absorbing powder was added, it was stirred in a double planetary mixer for 1.0h and the viscosity was adjusted to 2.5×10 5 mPa·s, after vacuum degassing.
[0047] Finally, the present invention extrudes component A and component B through an AB hose and an AB glue gun at a mass ratio of 1:1 to mix evenly, then vacuumizes the mixture to remove bubbles and presses it into a 2 mm sheet, and vulcanizes it at 120° C. for 0.5 h to obtain a test sheet sample (test results are shown in Table 1).
[0048] Table 1 Material properties
[0049] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A dispensing type thermally conductive and wave-absorbing gel, characterized in that: It is composed of component A and component B in a mass ratio of 1:1; The raw materials of component A include: 100 parts by weight of vinyl silicone oil, 0.4-0.6 parts by weight of catalyst, and 70-80 parts by weight of Fe / Al2O3 thermal conductive wave absorbing powder; The raw materials of the B component include: 20 parts by weight of hydrogenated silicone oil for chain extension, 80 parts by weight of hydrogenated silicone oil for cross-linking, 0.4-0.6 parts by weight of inhibitor, and 70-80 parts by weight of Fe / Al2O3 thermal conductive and wave absorbing powder.
2. The dispensing type thermal conductive wave absorbing gel according to claim 1, characterized in that: The viscosity of vinyl silicone oil is 100-1000 mPa·s, the viscosity of hydrogen-containing silicone oil for chain extension is 500-1000 mPa·s, and the viscosity of hydrogen-containing silicone oil for cross-linking is 10-200 mPa·s.
3. The dispensing type thermal conductive wave absorbing gel according to claim 1, characterized in that: The catalyst is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane.
4. The dispensing type thermal conductive wave absorbing gel according to claim 1, characterized in that: The inhibitor is 1-ethynylcyclohexanol.
5. The dispensing type thermal conductive wave absorbing gel according to claim 1, characterized in that: The preparation method of the Fe / Al2O3 thermal conductive wave absorbing powder is as follows: (1) 500 mL of deionized water, 1.0-5.0 g of Tween 40, and 50-55 g of micron-sized carbonyl Fe powder were added to a beaker in sequence, stirred for 10-24 h, and centrifuged to obtain Tween-modified carbonyl iron powder; (2) 100 ml of anhydrous ethanol, 10-12 g of Tween-modified carbonyl iron powder, 1-5 ml of triethylamine, and 2-3 ml of 0.1-1.0 mol / l ethanol aqueous solution of aluminum isopropoxide are sequentially added to a beaker, stirred evenly, filtered, and solids are collected; (3) washing the collected solid with ethanol or deionized water for multiple times and vacuum drying; finally, placing the dried product in a tubular furnace, calcining at high temperature, and collecting the product after cooling to room temperature to obtain Fe / Al2O3 thermal conductive and microwave absorbing powder.
6. The dispensing type thermal conductive wave absorbing gel according to claim 5, characterized in that: In step (2), the solvent ethanol aqueous solution in the ethanol aqueous solution of aluminum isopropoxide is prepared by mixing anhydrous ethanol and water in a mass ratio of 1:
1.
7. The dispensing type thermally conductive and wave absorbing gel according to claim 5, characterized in that: In step (3), high temperature calcination is: heating to 800-850°C at a heating rate of 10-20°C / min, and keeping warm for 2 hours under nitrogen protection.
8. The dispensing type thermal conductive wave absorbing gel according to claim 1, characterized in that: The processing method of component A is as follows: vinyl silicone oil, catalyst and Fe / Al2O3 heat-conducting and wave-absorbing powder are stirred and mixed in a double planetary mixer, and fumed silica is added to adjust the viscosity to 2.0×10 5 ~5.0×10 6 mPa·s, and finally vacuum degassing.
9. The dispensing type thermal conductive wave absorbing gel according to claim 1, characterized in that: The processing method of the B component is: stir and mix the hydrogenated silicone oil for chain extension, the hydrogenated silicone oil for cross-linking, the inhibitor and the Fe / Al2O3 heat-conducting and wave-absorbing powder in a double planetary mixer, add fumed silica to adjust the viscosity to 2.0×10 5 ~5.0×10 6 mPa·s, and finally vacuum degassing.
Citation Information
Cited By
Single-component heat-conducting wave-absorbing gel as well as preparation method and application thereof
CN121628381A